Obesity in women of reproductive age and its relation to polycystic ovarian syndrome and sub-fertility - Saadi Ali , Parween; Alsakkal, Ghada (Zanco Journal of Medical Sciences (ZJMS), 2024)
Background and objective: The Sub-fecundity and infertility are both enhanced by obesity. Regardless of the method of conception, obese women have less favourable reproductive results, and poorer fertility prognosis. One of the main reasons for infertility is polycystic ovarian syndrome (PCOS). The purpose of this study is to determine how obesity and polycystic ovarian syndrome affect fertility in women of reproductive age. Methods: A cross-sectional study was performed at a maternity teaching hospital in Erbil, Kurdistan Region, Iraq. It comprises 400 women: 200 with a BMI of 30 or above and 200 with a BMI between 18 and 24. From January 1, 2021, until December 31, 2021. Results: The average age of the enrolled women was 29.9 years. The majority (81.5%) were under 30 years of age, and (70.6%) were classified as overweight. In the obese group, 55% of women had never experienced pregnancy. A greater percentage of the obese group had no history of miscarriage in comparison to the non-obese group. The obese group exhibited a significantly higher prevalence of hirsutism (59%) compared to the non-obese group (39.5%). Infertility rates varied from 84% in the obese group to 38.5% in the non-obese group. In contrast to 44.5% of non obese women, the ultrasonographic findings indicated that 60% of obese women displayed PCOS morphology. Conclusion: Obesity has effect on the occurrence of sub-fertility and polycystic ovary syndrome at all reproductive ages.